Coexisting rheumatoid arthritis and sickle cell disease: case series and literature review - Abdallah Alqethami; Sabri Alsaeedi; Samera Felemban; Abdulelah Qadi (Reumatismo)
Rheumatoid arthritis (RA) is rarely reported among patients with sickle cell disease (SCD). RA treatment in these patients is believed to be more challenging due to fear of increasing the risk of infection and complications of SCD. We are reporting 7 patients with concurrent SCD and RA. The average age at the time of the diagnosis of RA was 33.3±12.6 years (ranging from 16 to 53 years), and most were women (5/7). Most of the patients were positive for rheumatoid factor (6/7) or anticyclic citrullinated peptide (6/7). Four patients were treated with hydroxyurea. The most used antirheumatic drugs were methotrexate (7/7), biologic agents (5/7), and prednisone (4/7). Two patients were in remission, four had low and one had high disease activity. Four patients (4/7) had avascular necrosis, two in the shoulders and two in the hip joints. Four patients had emergency visits or hospitalizations within one year of the diagnosis of RA, but none had blood transfusions, infections, or death. The start of antirheumatic medication was not associated with an increased risk of infection, blood transfusions, emergency visits, or hospitalizations, nor with a worsening of laboratory measures. The findings suggest that the treatment of RA in patients with SCD should follow the same strategy as in patients without SCD. However, treatment should be individualized according to the individual patient's risk of infection and SCD complications.